QoS-Guaranteed Power Control Mechanism Based on the Frame Utilization for Femtocells - Mach Pavel; Becvar Zdenek (EURASIP Journal on Wireless Communications and Networking, 2011)
The paper focuses on a power control mechanism and proposes a novel approach for dynamic adaptation of femtocells' transmitting power. The basic idea is to adapt the transmitting power of femtocells according to current traffic load and signal quality between user equipments and the femtocell in order to fully utilize radio resources allocated to the femtocell. The advantage of the proposed scheme is in provisioning of high quality of service level to the femtocell users, while interference to users attached to macrobase station is minimized. The paper proposes the power adaptation algorithm and evaluates its performance in terms of mobility events, achieved throughput, and FAPs transmitting power. Performed simulations show that the proposed scheme can significantly reduce the number of mobility events caused by passerby users and thus to minimize signaling overhead generated in the network. In addition, our proposal enhances overall throughput for most of the investigated scenarios in comparison to other power control schemes.